Machine learning and deep learning in medical data analytics and healthcare applications - Jena, Om Prakash; Bhushan, Bharat; Kose, Utku, 1985- (Boca Raton : CRC Press, 2022)
"The book incorporates the many facets of computational intelligence, such as machine learning and deep learning, to provide groundbreaking developments in healthcare applications. It discusses theory, analytical methods, numerical simulation, scientific techniques, analytical outcomes, and computational structuring"--
1. Common Data Interface for Sustainable Healthcare System. Abhilash C B, K.T Deepak, Rajendra Hegadi and Kavi Mahesh2. Brain-Computer Interface: Review, Applications and Challenges.Prashant Sengar and Shawli Bardhan3. Three Dimensional Reconstruction And Digital Printing Of 3D Medical Objects In Purview Of Clinical Applications. Sushitha Susan Joseph and Aju D4. Medical Text And Image Processing: Applications, Issues And Challenges. Behzad Soleimani Neysiani and Hassan Homayoun5. Usage Of Ml Techniques For Asd Detection: A Comparative Analysis Of Various Classifiers. Ashima Sindhu Mohanty,Priyadarsan Paridaand Krushna Chandra Patra6. A Framework For Selection Of Machine Learning Algorithms Based On Performance Metrices And Akaike Information Criteria In Healthcare, Telecommunication, And Marketing Sector. Abubakar Kamagata Hamisu and Jasleen Kaur7. An Improved Marine Predators' Algorithm With Simulated Annealing For Feature Selection In The Medical Field. Utkarsh Khaire, R Dhanalakshmi and Balakrishnan K8. Survey Of Deep Learning Methods In Image Recognition And Analysis Of Intrauterine Residues. Bhawna Swarnkar, Dr. Nilay Khare and Dr. Manasi Gyanchandani9. A Comprehensive Survey On Breast Cancer Thermography Classification Using Deep Neural Network. Amira Hassan Abed, Essam M Shaaban, Om Prakash Jena, Ahmed A. Elngar10. Deep Learning Frameworks For Prediction, Classification And Diagnosis Of Alzheimer's Disease. Nitin Singh Rajput, Mithun Singh Rajput and Purnima Dey Sarkar11. Machine Learning Algorithms And Covid-19; A Step For Predicting Future Pandemics: A Systematic Overview. Madhumita Pal, Kuldeep Dhama, Smita Parija, Om Prakash Jena and Ranjan K. Mohapatra12. Trnetcov: Transferred Learning Based Resnet Model For Covid-19 Detection Using Chest X-Ray Images. G V Eswara Rao and Rajitha B13. The Influence Of Covid-19 On Air Pollution And Human Health. Loubna Bouhachlaf, Jamal Mabrouki and Souad El Hajjaji14. Smart Covid-19 Geostrategies Using Spatial Network Voronoï Diagrams. Aziz MabroukandAzedine Boulmakoul15. Healthcare Providers Recommender System Based On Collaborative Filtering TechniquesYousef Farhaoui
OCLC-licensed vendor bibliographic record.
Keywords: Medical technology; Medical care -- Technological innovations; Robotics in medicine; COMPUTERS / Machine Theory; MEDICAL / Hospital Administration & Care; SCIENCE / Biotechnology